Analysis of UBSI Students’ Satisfaction with the SIAKAD Student Website Using the PIECES Method - Kholifah, Desiana Nur; Mulya, Danu (LPPM STMIK Dharmapala Riau, 2026)
Universitas Bina Sarana Informatika (UBSI) has developed an Academic Information System (SIAKAD) as a tool to support academic activities. Students use this system to update personal information, access course registration (KRS), academic transcripts (KHS), and other academic-related information. Although the system offers fairly comprehensive functionality and facilitates accurate information access for both students and lecturers, SIAKAD still faces several issues such as bugs, an unintuitive user interface, and performance degradation during peak usage. For instance, during grade announcements when many users access the system simultaneously, it often slows down, experiences long page loading times, or even crashes due to server overload. This study aims to evaluate the UBSI Student SIAKAD website using the PIECES analysis method, which includes aspects of Performance, Information, Economics, Control, Efficiency, and Service. Through this approach, a comprehensive overview of the system's strengths and weaknesses can be obtained. The analysis results indicate that, overall, students are satisfied with the performance, ease of use, and reliability of the SIAKAD website. This conclusion is expected to serve as a foundation for future system development and improvements to better support academic activities within UBSI.